Estimates of economic values for important traits of two indigenous Ethiopian sheep breeds - Gebre, K.T.; Fuerst-Waltl, B.; Wurzinger, Maria; Philipsson, J.; Duguma, G.; Mirkena, T.; Haile, Aynalem; Sölkner, Johann (Elsevier, 2012)
A bio-economic model was adapted to estimate economic values for important traits of two Ethiopian indigenous sheep breeds, the Menz and Horro breeds. To do so, a meat sheep herd for fattening lambs and rearing young replacement sheep was simulated. Traits included in the analysis were: daily gain (fattening trait), live weight of ewes, length of productive life, lambing interval, litter size, stillbirths and lamb survival (functional traits). To avoid double counting, the economic value for each trait was derived while keeping all other traits constant. Economic values were obtained per ewe place, year, and genetic standard deviation. For the Menz breed, economic values in € per genetic standard deviation were 0.63 (daily gain), −0.77 (mature ewe live weight), −0.97 (length of productive life), 1.57 (lambing interval), 0.98 (litter size), 0.41 (stillbirths) and 2.20 (lamb survival). Economic values (in €) of 1.35 (daily gain), −1.26 (mature ewe live weight), −1.15 (length of productive life), 1.98 (lambing interval), 3.67 (litter size), 0.56 (stillbirth) and 3.25 (lamb survival) were derived for the Horro breed. Negative economic values for length of productive life and mature ewe live weight were estimated for both breeds. After setting the economic values of length of productive life and mature ewe live weight to zero, the economic values (in %) for the ratio of the trait complexes fattening: functional traits were 11:89 and 12.5:87.5 for Menz and Horro, respectively. Economic values for litter size, lambing interval and lamb survival traits were sensitive to changes in price for breeding rams in both breeds.